2021
DOI: 10.3390/ijms22126274
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility to Periodontal Disease in Down Syndrome: A Case-Control Study

Abstract: Severe periodontitis is prevalent in Down syndrome (DS). This study aimed to identify genetic variations associated with periodontitis in individuals with DS. The study group was distributed into DS patients with periodontitis (n = 50) and DS patients with healthy periodontium (n = 36). All samples were genotyped with the “Axiom Spanish Biobank” array, which contains 757,836 markers. An association analysis at the individual marker level using logistic regression, as well as at the gene level applying the sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 54 publications
0
9
0
1
Order By: Relevance
“…This is the first bioinformatics study, which investigated the potential crosstalk between DS and periodontitis. A genetic crosstalk between periodontitis and DS has been repeatedly discussed in literature [ 8 10 , 15 , 16 ]. This has been evaluated in the current study, whereby the hypothesis of a potential crosstalk between these two diseases was confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is the first bioinformatics study, which investigated the potential crosstalk between DS and periodontitis. A genetic crosstalk between periodontitis and DS has been repeatedly discussed in literature [ 8 10 , 15 , 16 ]. This has been evaluated in the current study, whereby the hypothesis of a potential crosstalk between these two diseases was confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…This has been evaluated in the current study, whereby the hypothesis of a potential crosstalk between these two diseases was confirmed. Thereby, a recent case-control study identified single nucleotide polymorphisms (SNP) to be significantly associated to periodontal disease in DS individuals, underlining the relevance of shared genetic mechanisms [ 15 ]. It has also been found in that clinical study that different metabolic pathways, including the PI3K-Akt signaling pathway, would play an important role in this context [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations